Mutational analysis of the Portuguese cohort with clinical diagnosis of FH - Medeiros, A.M. (2014)
INTRODUCTION : Familial hypercholesterolemia (FH) is a common autosomal dominant disorder of lipid metabolism (1:500 frequency), caused by mutations in genes involved in cholesterol’s clearance. FH patients present high levels of plasma cholesterol since birth, and if untreated, develop premature coronary heart disease (pCHD). The aim of the Portuguese FH Study is to promote the early identification and characterization of FH patients in order to decrease their cardiovascular risk by the implementation of correct/adequate and early counselling/treatment.